2021
DOI: 10.1097/ncc.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Do COVID-19–Related Treatment Changes Influence Fear of Cancer Recurrence, Anxiety, and Depression in Breast Cancer Patients?

Abstract: BackgroundThe worldwide spread of the coronavirus disease 2019 (COVID-19) has impacted the treatment of cancer patients. Treatment changes can negatively affect patients’ prognosis and may be psychologically burdensome.ObjectiveThe aim of this study was to explore whether COVID-19–related treatment changes (delays, cancellations, changes) influenced fear of cancer recurrence, anxiety, and depression in breast cancer patients.MethodsA convenience sample (n = 154) of patients who were diagnosed with breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…Furthermore, 35.7% of the participants assessed in this study attained severity scores higher than 22, suggesting that over one third of the participants experienced a clinically significant level of fear of cancer recurrence. This result was compared with the results obtained on similar populations, assessed with the same instrument in non-Covid-19 periods, and the results indicated that the number of the participants assessed in the Kim and Kim's [ 48 ] study, who reported clinically significant values of FCR (meaning 22 points) was twice as high. However, as the authors have emphasized, these differences have to be interpreted with caution because the previous study to which they compared their results involved older participants, the period of time between diagnosis and assessment was longer, and was conducted before the pandemic.…”
Section: Breast Cancermentioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, 35.7% of the participants assessed in this study attained severity scores higher than 22, suggesting that over one third of the participants experienced a clinically significant level of fear of cancer recurrence. This result was compared with the results obtained on similar populations, assessed with the same instrument in non-Covid-19 periods, and the results indicated that the number of the participants assessed in the Kim and Kim's [ 48 ] study, who reported clinically significant values of FCR (meaning 22 points) was twice as high. However, as the authors have emphasized, these differences have to be interpreted with caution because the previous study to which they compared their results involved older participants, the period of time between diagnosis and assessment was longer, and was conducted before the pandemic.…”
Section: Breast Cancermentioning
confidence: 85%
“…However, as the authors have emphasized, these differences have to be interpreted with caution because the previous study to which they compared their results involved older participants, the period of time between diagnosis and assessment was longer, and was conducted before the pandemic. According to this study, FCR was significantly higher among participants that were not married (F = 3.649, p = .028 ), childless (t = −2.043, p = .043 ) less financially potent participants (F = 4.259, p = .016 ) [ 48 ].…”
Section: Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations